Biogas Production from a Mix of Cow Manure with Odot Grass (Pennisetum purpureum cv. Mott) - Pebry Angga Putra Sandy; Vivi Indriani; Monasdir (Jurnal Peternakan Integratif, 2025)
Biogas is one of the alternative energy sources that can be updated because it uses raw materials derived from livestock manure. The research aims to analyze biogas production from a mixture of odot grass and cow manure. The study was conducted with 3 treatments namely 100% cow manure (control), 70% cow manure + 30% odot grass, and 50% cow manure + 50% odot grass. The parameters are temperature, degree of acidity, total solid and volatile solids, volume biogas, flame test, and C and N content measurement. The research design used was a Completely Randomized Design (CRD) Each treatment was repeated three times. The results showed that the mixture of cow manure biogas with odot grass was very real (P<0.05) against the production of biogas produced successive production values for M₁₀₀G₀, M₇₀G₃₀, and M₃₀G₃₀ 191.3500 mL; 99,0067 mL and 0.0000 mL. The C/N ratio of each treatment is 27.52; 25.32 and 23.85. The average daily temperature is about the same for all treatments which is 27-29°C. The pH value of each treatment is 5.90-7.27; 5.00-7.00 and 4.77-6.70. The content of TS, VS the initial and final of each treatment is the initial TS of 11,014; 11,007; and 11,195; final TS 6,960; 6,794; and 6,714; initial VS 8,838; 8,965; and 9,309; final VS of 5734; 5,728; and 5,831. Biogas flames with a mixture of odot grass (M₁₀₀G₀) dan (M₇₀G₃₀) produce blue biogas flames (M₅₀G₅₀) do not produce flames.  A mixture of odot grass and cow dung as a substrate did not produce high levels of biogas, compared to the non-odot grass mixture, which produced higher biogas production